Respuesta :

Answer:

A. 10m - 16

Step-by-step explanation:

First, distribute 3 to all terms within the corresponding parenthesis, and -2 likewise:

3(4m - 2) =

3 * 4m = 12m

3 * -2 = -6

3(4m - 2) = 12m - 6

-2(m + 5) =

-2 * m = -2m

-2 * 5 = -10

-2(m + 5) = -2m -10

Combine like terms:

12m - 6  -2m - 10

12m - 2m - 6 - 10

(12m - 2m) + (-6 - 10)

10m - 16

A. 10m - 16 is your answer.

~

Answer:

10 m - 16 (Answer A)

Step-by-step explanation:

We use distributive property to eliminate parenthesis:

12 m - 6 - 2 m -10

and now combine like terms:

[12 m - 2 m] - 6 - 10

10 m - 16

Therefore, answer option A.  is the correct one

ACCESS MORE